Valores de referência para espirometria na população brasileira: uma revisão de escopo - Souza, Helen Debora Guedes de (Brasil, 2025)
Introduction: Spirometry is essential for assessing lung function and diagnosing respiratory diseases. In Brazil, ethnic diversity and demographic and geographic characteristics make it necessary to develop specific reference values for the Brazilian population. Objectives: To summarize the scientific evidence on spirometry reference values for the Brazilian population. Methods: A scoping review was conducted following the JBI Collaboration methodology and the PRISMA-ScR checklist. Studies with (apparently) healthy Brazilians, regardless of age, sex, and race/color, that provided reference values for spirometry were included. The search covered databases such as PubMed, CINAHL, Embase, LILACS, SciELO, Scopus, Web of Science, SPORTDiscus, and PEDro, in addition to gray literature sources, from the start of each database’s indexing until May 12, 2024, in any language. Studies were selected using Rayyan, and data extraction was performed with a custom form. Results: Eight studies were selected, totaling 3,108 healthy participants aged 3 to 75 years, from two regions of Brazil, predominantly the Southeast region. Spirometry values varied according to age, sex, and skin color. Among adults, differences in FVC and FEV1 values were observed between men and women. In children, variations were influenced by growth. Fifteen reference equations were identified, mostly linear and logarithmic, considering factors such as age, height, weight, and skin color, highlighting the relevance of these variables in determining lung function reference values for the Brazilian population. Conclusion: The reference values for spirometry in Brazil are limited and do not reflect the ethnic, age, and regional diversity, with studies concentrated in the Southeast and South, focusing on white individuals.